Use of Problem-Based Electronic Worksheet on Hooke's Law Materials to Increase Creativity of Students - I Dewa Putu Nyeneng; Chandra Ertikanto; Agus Suyatna; I Komang Astawan (Jurnal Pembelajaran Fisika, 2022)
This research aims to find out the use of problem-based Electronic worksheets with problem-based learning models in Hooke's Law subject material to increase the creativity of students. The population of this study was all students of class XI IPA State High School 1 Rumbia. The sample in this study of students was in class XI IPA 1 amounted to 34 as an experimental class, and students in class XI IPA 2 numbered 34 as the control class. The research design used was the Non-Equivalent Pretest Posttest Control Group Design. The data were tested with N-gain analysis, normality test, homogeneity test, Independent Sample T-test, and Effect Size test. Based on research that has been done, using the Independent Sample T-test sig value. (2-Tailed) less than 0.05 which was 0.00. The average N-gain of experimental class critical skills of 0.76belonged to the high category, while in the control class of 0.61 it was included in the medium category. Based on the effect size test obtained results of 1.39 showed that the use of a problem-based electronic worksheet with a problem-based learning model was effective to increase the creativity of students.Keywords: Creativity, Electronic Worksheet, PBLDOI: http://dx.doi.org/10.23960/jpf.v10.n1.202207